Resilience processes in sexually abused adolescent girls: A scoping review of the literature - Sadiyya Haffejee; Linda Theron (South African Journal of Science, 2017)
Childhood sexual abuse is often associated with a number of deleterious psychological and behavioural outcomes for survivors. However, some research suggests that this impact is variable and that some survivors adapt positively. An ability to adapt positively to adversity, under any circumstances, has been termed resilience. Drawing on a socio-ecological understanding of resilience, the aim of this scoping review was to comprehensively map existing empirical studies on resilience processes in sexually abused adolescent girls and to summarise emerging resilience-enabling factors. We also considered the implications of the findings for practice and research. A total of 11 articles met the criteria for inclusion in the review. Findings from these studies suggest that internal factors (meaning making, optimistic future orientation, agency and mastery) and contextual factors (supportive family, social and educational environments) function interdependently to enable resilience in sexually abused adolescent girls. Practitioners should leverage these complementary and interdependent resilience-enabling mechanisms by encouraging greater involvement of girls in the planning of interventions and by assisting girls in developing meaningful narratives about their abuse experiences. Interventions should also encourage greater involvement from supportive structures, while challenging social and cultural norms that inhibit resilience. Resilience researchers should be cognisant of the paucity of research focusing on resilience processes in sexually abused adolescent girls as well as the absence of innovative, participatory methods of data collection.